Assessment of Sensorineural Hearing Loss in Patients with Hypothyroidism and its Relationship with Thyroid Stimulating Hormones Levels: A Cross-Sectional Study - Lt Col Ghulam Fareed, Asad Ali, Ali Murtaza, Hassan Raza Naqvi, Haitham Akaash, Inam- Ul-Haq (Pakistan Journal of Medical & Health Sciences, 2023)
Background: The auditory system needs thyroid hormone to develop normally. Additionally, endemic cretinism and people with thyroid hormone resistance have also been linked to hearing loss. Congenital hypothyroidism (CH) and hearing impairment (HI) have been linked in earlier studies. Objective: This study was conducted to assess the sensorineural hearing loss in patients with hypothyroidism and its relationship with thyroid stimulating hormones levels. Study Design: It was a cross-sectional study. Study Duration: The study was conducted at department of ENT CMH, Multan from 01 January 2022 to 30th October 2022. Material and Methods: Sample size of 150 patients who were diagnosed with hypothyroidism were included through convenient sampling. Patients with external or middle ear inflammation or obstruction, as well as those who were unable to complete pure tone audiometry, were not included. Once participants gave their informed consent, a standard medical history and demographics form was used to compile data, and an audiogram was then performed to round out the picture. The data was analysed using SPSS version 22.0. Results: There were a total of 150 patients who participated in the study. The average age of patients who had hearing loss was 38.19 years old. Only 15.16% of patients were male, while 83.98% were female. Tinnitus was experienced by 11 people in their right ears and 10 in their left ears. Twenty (95.24%) patients reported having tinnitus for less than a year when they first visited our clinic. The duration of hypothyroidism in 36.7% of patients who presented to us was between 1 and 12 months, 32% between 13 and 24 months, 18.2% between 25 and 36 months, and 13.3% for more than 36 months. TSH levels ranged from 4.5 to 5.0 in 38 (62.29%) of the individuals with hearing loss, from 5.1 to 5.5 in 8 (13.11%), from 5.6 to 6.0 in 7 (11.47%), and from 6.1 to 6.5 in 8 (13.11%). Prolonged hypothyroidism has been shown to have an effect on hearing loss severity, as indicated by a significant statistical correlation (P value 0.001). Practical implication: This study is very important since its findings may enable researchers to carry out in-depth studies in the area with objectives. Pakistan has to conduct more research on the critical issue of SSNHL. Conclusion: According to the findings of our research, hypothyroidism has an effect on patient’s hearing, which can lead to hearing impairment. Keywords: Thyroid function test, Hypothyroidism, Sensorineural hearing loss, Hormones Levels